The influence of verbal commands corresponding with the kinaesthetic impulses on precision of movements among children in younger age - Zaton, K.; Klarowicz, A. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The aim of this work was to establish if during the teaching process of swimming movements, the simple verbal command together with explanation of the kinestetic impulses adressed to the pupils while the actual body movements in water, influences the efficiency of learning. The aim of this work had been veryfied by natural experiment.